Analisis Titik Tertinggi dan Terendah dengan Model Stokastik pada Perdagangan Mata Uang Modern - Raymond Sunardi Oetama (Universitas Multimedia Nusantara, 2016)
The Internet supports a new era of trading online in foreign Exchange Market. One of popular pairs in this market is Gold which is paired with US Dollars or commonly coded as XAUUSD. Prices are drawn as candle sticks. These candle sticks have four data such as open, low, high, and close price. The highest and the lowest price are explored in this study using Stochastic. The highest and lowest price is interesting to be analyzed as Traders can make maximum profit by trading from the highest price to the lowest price or vice versa. Index Terms—forex, gold, candle sticks, statistics, stochastics